PENGUKURAN TINGKAT KINERJA RUAS JALAN MENGGUNAKAN DATA GPS - Rusmadi Suyuti; Mulyadi Sinung Harjono (Forum Studi Transportasi antar Perguruan Tinggi (FSTPT), 2013)
In addition to the volume to road capacity ratio, another indicator for the level of service of the road is the average traffic speed. Once the road capacity is exceeded, the lower the average traffic speed means the worse the performance of the road. The traffic speed information is also required as an input to the Real Time Traffic Information System. This purpose of this study is to measure the average traffic speed on a road segment using information obtained from the Global Positioning System. Off - roadway technologies using satellite technology have advantages in managing information position, direction and movement speed. In this observation a test vehicle equipped with the Global Positioning System moved along the urban road network and monitored in real time from a Control Center. When the position data of the test vehicles Control Center can connect directly with road network information system, the average traffic speed on the road can be obtained in real time condition. In addition as an indicator of the level of service of the road, with an average speed data, it can also be used for predicting traffic volume in an urban road network.Keywords: traffic speed, Global Positioning System, level of service of roads, traffic information system